The impact of monetary policy and its surprises on bank’s risk-taking - Gaudêncio, João miguel Bravo (2018)
The latest financial crisis accentuated the importance of understanding bank risk and its ties to financial stability. This paper looks to investigate the impact of monetary policy in the risk-taking behaviour of Euro Area banks, when taking unconventional monetary policy into account. Looking further into this relationship, the impact of unanticipated monetary policy shocks is also analysed. Using both fixed effects and a system GMM model, sufficient statistical evidence was found to claim that looser monetary policy leads to increased risk-taking behaviour from banks. This effect, however, is mitigated in case banks and/or the market originally anticipated an even looser stance by the central bank.